The Role of Annealing Temperature on the Optical Properties of Thermally Deposited CdTe Films - Al-Douri, A. A. (Iraqi Journal of Physics, 2011)
A polycrystalline CdTe film has been prepared by thermal evaporation technique on glass substrate at substrate temperature 423 K with 1.0 m thicknesses. The film was heated at various annealing temperature under vacuum (Ta =473, 523 and K). Some of physical properties of prepared films such as structural and optical properties were investigated. The patterns of X-ray diffraction analysis showed that the structure of CdTe powder and all films were polycrystalline and consist of a mixture of cubic and hexagonal phases and preferred orientation at (111) direction.The optical measurements showed that un annealed and annealed CdTe films had direct energy gap (Eg). The Eg increased with increasing Ta. The refractive index and the real part of dielectric constant for films were observed to decrease with increasing Ta, while the extinction and the imaginary part of dielectric were increased. Our result is good candidate for manufacturing optoelectronic device such as solar cells.